Experimental Study On Partial Replacement Of Cement By Prosopis Juliflora Ash And Fine Aggregate By Steel Slag - Dr. K. Karthikeyan*, Dr. N. Nagarajan, Dr. S.Sivaprakasam, G. S. Saravanakumar , K. Shakila (International Journal of Advanced Science and Technology, 2020)
This study aims at evaluating the recital of concrete by substituting cement partially with prosopis Juliflora Ash and sand with Steel-Slag. It is a manufacturing waste that is created in the course of production of steel. In India, annual production of it is about 10 Million Tonne. It is very important that we need to utilize these waste in order to avoid the land pollution. Therefore, replacing some of the natural aggregate by Steel-Slag would result in substantial environmental profit. The Prosopis Juliflora Ash means residue left after the combustion of wood, from burning wood at home, hotels or industries. This residue is a difficult substance to get decomposed and it absorbs more groundwater. Therefore, using the PJA as a partial substitute of cement can provide a green and clean environment. In this project work, Prosopis Juliflora Ash with the ratio in percentage of about 2.5, 5, 7.5 and 10 is replaced for cement and 10, 20, 30 and 40 percentage of steel-slag used partially as substitute of sand. The mechanical characteristics in concrete like compressive strength, tensile strength and workability has been assessed. The appropriate and shared percentage was established to be 7.5 of PJA and 30 of SS. The study outcome in percentage tells that 7.5 of PJA and 30 of SS improve the strength of concrete in comparison with other alternatives.